2019
DOI: 10.1097/sla.0000000000003663
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Impact of High Vascular Tie After Surgery for Rectal Cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 39 publications
0
30
0
3
Order By: Relevance
“…Several other studies have also shown that the incidence of metastatic apical lymph nodes ranges from 0.3% to 8.6%[ 22 - 25 ]. Boström et al[ 7 ] recently published a nationwide cohort study and showed that the level of ligation did not influence the oncological outcome or overall survival. Sakamoto et al[ 26 ] investigated the potential impact of the lymph-vascular microanatomy of the IMA, and their findings partially support the surgical concept of LCA preserving lymph node dissection around the IMA due to potential metastasis in the lymphatic ducts within the IMA sheath.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have also shown that the incidence of metastatic apical lymph nodes ranges from 0.3% to 8.6%[ 22 - 25 ]. Boström et al[ 7 ] recently published a nationwide cohort study and showed that the level of ligation did not influence the oncological outcome or overall survival. Sakamoto et al[ 26 ] investigated the potential impact of the lymph-vascular microanatomy of the IMA, and their findings partially support the surgical concept of LCA preserving lymph node dissection around the IMA due to potential metastasis in the lymphatic ducts within the IMA sheath.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, some scholars believe that LL can reduce the incidence of postoperative complications, especially the anastomotic leakage (AL) rate; however, other studies suggest that HL can obtain a higher lymph node yield, and shorten the operation time, without having any effect on the AL[ 4 - 6 ]. A recent nationwide cohort study in Sweden showed that the ligation level did not influence patients’ overall survival and oncological outcomes[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a retrospective analysis [67] including 890 patients showed that LL of the IMA with ALN dissection was not inferior to HL in terms of oncological prognosis. Besides, a large, nationwide cohort study [68], which was reported by Boström et al and included 8287 rectal cancer patients, showed an increased lymph node yield with HL, but failed to reveal an association between the level of ligation and long‐term survival outcomes. Furthermore, no significant difference in the 5‐year overall survival rate was found between the HL group and the LL group with ANL dissection in one included RCT [24] in which the 5‐year overall survival rate was the secondary outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled analysis also showed that LL of the IMA with ALN dissection did not compromise the number of harvested lymph nodes compared with HL, although the quality of evidence was very low. Additionally, a retrospective analysis [67] including 890 patients showed that LL of the IMA with ALN dissection was not inferior to HL in terms of oncological prognosis. Besides, a large, nationwide cohort study [68], which was reported by Boström et al and included 8287 rectal cancer patients, showed an increased lymph node yield with HL, but failed to reveal an association between the level of ligation and long-term survival outcomes.…”
Section: Ta B L E 1 Study Characteristics For the Included Trialsmentioning
confidence: 97%
“…On the one hand, the impact of preserving the LCA on the development of AL in rectal cancer patients following anterior resection remains controversial [ 12 14 ]. Another point of debate is whether LCA preservation affects lymph node (LN) dissection and oncological outcomes [ 15 , 16 ]. Since the benefits of LCA preservation are debatable, robust evidence of the outcomes of LCA preservation plus apical LN dissection is lacking.…”
Section: Introductionmentioning
confidence: 99%